Eksplorasi Dan Pengujian Tumbuhan Obat Masyarakat Kecamatan Merawang Sebagai Peningkat Imun Dan Makanan - Riko Irwanto; Agustara Dwi Juwita; Luffi Pratiwi; Fifi Lestari (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
This study aims to determine the types and parts of herbal medicinal plants used as immune boosters and food by the people of Merawang District and to determine the content of chemical compounds in medicinal plants used as immune enhancers and food by the people of Merawang District. This research was conducted in September-November 2021. Samples were obtained from 5 villages (Balunijuk village, Pagarawan village, Jada Bahrin village, Jurung village, and Kimak village) in Merawang District, Bangka Regency, Bangka Belitung Islands Province. The results showed that medicinal plants found in 5 villages in Merawang sub-district (Balunijuk village, Pagarawan village, Jada Bahrin village, Jurung village, and Kimak village) contained 6 types of plants and their family names Akar Medang Sahang (Lauraceae), Pepper (Piperaceae), Coriander roots, Kecapa stems (Asteraceae), Pandan roots & Belacan stems (Pandanaceae & Verbenaceae) have the potential to cure various diseases, one of which is overcoming problems with ulcers, stomach acid, jaundice, and impotence. Parts of the plant used start from the roots, stems, to leaves. The results of the TLC method showed that each extract contained active secondary metabolites, namely alkaloids, flavonoids, and triterpenoids.